Effect of seed treatment with insecticides on the control of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in soybean - Triboni, Yago Barros [UNESP]; Del Bem, Luciano [UNESP]; Raetano, Carlos Gilberto [UNESP]; Negrisoli, Matheus Mereb [UNESP] (Instituto Biológico, 2019)
Fall armyworm is one of the main insect pests in Brazil. Thus, the present work aimed to evaluate the seed treatment effect on the control of Spodoptera frugiperda in initial infestations of soybean crops. The experimental design was completely randomized with four replicates of six insecticide treatments applied through seed treatment: imidacloprid plus thiodicarb at the dose of 52.5 plus 105 g a.i. (active ingredient) 100 kg-1 of seed (Cropstar® 0.350 L 100 kg-1 of seed); thiamethoxam at 105 g a.i. 100 kg-1 of seed (Cruiser 350 FS® 0.3 L 100 kg-1 of seed); chlorantraniliprole at 62.5 g a.i. 100 kg-1 of seed (Dermacor® 0.1 L 100 kg-1 of seed); cyantraniliprole at 120 g a.i. 100 kg-1 of seed (Fortenza 600 FS® 0.2 L 100 kg-1 of seed); fipronil plus pyraclostrobin and thiophanate-methyl 50 + 5 + 45 g a.i. 100 kg-1 of seed (Standak Top® 0.2 L 100 kg-1 of seed), and a control treatment. The experiment was carried out in a greenhouse. Diamide insecticides (chlorantraniliprole and cyantraniliprole) presented the best results among all treatments, with lower consumption of the treated leaves by the caterpillars and greater control efficacy of this insect. We verified that seed treatment is a viable alternative for controlling S. frugiperda at the beginning of crop development, when the caterpillar presents the behavior of cutting the seedlings and/or the consumption of leaf area, causing a reduction in the plant population and a consequent yield loss.

A lagarta-do-cartucho é um dos principais insetos-praga no Brasil. Assim, o presente trabalho teve por objetivo avaliar o efeito do tratamento de sementes no controle de Spodoptera frugiperda nas infestações iniciais da cultura da soja. O delineamento experimental foi inteiramente casualizado, com quatro amostras replicadas de seis tratamentos inseticidas aplicados via tratamento de sementes: imidacloprida mais tiodicarbe na dose de 52,5 mais 105 g i.a. (ingrediente ativo) 100 kg-1 de sementes (Cropstar® 0,350 L 100 kg-1 de sementes); tiametoxam a 105 g i.a. 100 kg-1 de sementes (Cruiser 350 FS® 0,3 L 100 kg-1 de sementes); clorantraniliprole a 62,5 g i.a. 100 kg-1 de sementes (Dermacor® 0,1 L 100 kg-1 de sementes); ciantraniliprole a 120 g i.a. 100 kg-1 de sementes (Fortenza 600 FS® 0,2 L 100 kg-1 de sementes); fipronil mais piraclostrobina e tio-fanato-metílico 50 + 5 + 45 g i.a. 100 kg-1 de sementes (Standak Top® 0,2 L 100 kg-1 de sementes) e um tratamento controle. O experimento foi conduzido em uma vegetação. Dentre todos os tratamentos, os inseticidas do grupo químico das diamidas (clorantraniliprole e ciantraniliprole) apresentaram os melhores resultados, com consumo inferior pelas lagartas das folhas tratadas e maior eficiência de controle deste inseto. Foi constatado que o tratamento de sementes é uma alternativa viável para o controle de S. frugiperda no início do desenvolvimento da cultura, quando a lagarta apresenta o comportamento de cortar as plântulas e/ou consumir área foliar, ocasionando uma redução da população de plantas e uma consequente perda de produtividade.
Efeito do tratamento de sementes com inseticidas no controle de Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) na cultura da soja
Keywords: chemical control; diamide; fall armyworm; mortality; controle químico; diamidas; lagarta-do--cartucho; mortalidade.